2013
DOI: 10.1097/sla.0b013e3182778089
|View full text |Cite
|
Sign up to set email alerts
|

Should Patients With Peritoneal Carcinomatosis of Colorectal Origin With Synchronous Liver Metastases Be Treated With a Curative Intent? A Case-Control Study

Abstract: This case-control study seems to confirm that prolonged survival can be achieved in highly selected patients operated on for limited PC and fewer than 3 LM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(76 citation statements)
references
References 26 publications
8
65
0
3
Order By: Relevance
“…A meta-analysis conducted by Dutch investigators showed a trend toward lower OS after curative resection plus HIPEC in patients with CRC metastases in the liver, as well as in the peritoneum, than in patients with peritoneal metastases alone after the same treatment [48]. Although this approach can be used to treat PC and liver metastases during the same procedure in selected patients, only patients who have limited peritoneal spread (PCI < 12) and a limited extent of liver disease (liver metastases < 3) really benefit from this approach, with a median survival of 40 months [49].…”
Section: Extent Of Diseasementioning
confidence: 96%
“…A meta-analysis conducted by Dutch investigators showed a trend toward lower OS after curative resection plus HIPEC in patients with CRC metastases in the liver, as well as in the peritoneum, than in patients with peritoneal metastases alone after the same treatment [48]. Although this approach can be used to treat PC and liver metastases during the same procedure in selected patients, only patients who have limited peritoneal spread (PCI < 12) and a limited extent of liver disease (liver metastases < 3) really benefit from this approach, with a median survival of 40 months [49].…”
Section: Extent Of Diseasementioning
confidence: 96%
“…However, because the prognosis for colorectal cancer patients with limited resectable liver metastases after hepatic surgery and current chemotherapeutic regimens is reasonable, some centres will use liver surgery, crs, hipec, and systemic chemotherapy to treat patients with up to 3 peripherally localized and resectable liver metastases and limited ptc. The morbidity and long-term results in such patients are not different from those of colorectal ptc patients without liver metastases (to be discussed shortly) [12][13][14] . Infiltration of the liver capsule by peritoneal tumour should be differentiated from parenchymal liver metastases.…”
Section: Patient Selectionmentioning
confidence: 99%
“…As already discussed, patients with limited ptc and fewer than 3 resectable liver metastases can also be good candidates for hipec, with a reasonable possibility of achieving prolonged survival [12][13][14] .In a recent case-control study 13 , 37patients with ptc and liver metastases were matched with 61 patients having ptc alone. All underwent crs, resection of liver metastases (when present), and hipec.…”
Section: Colorectal Cancermentioning
confidence: 99%
“…In terms of a surgical approach, CRC for oligometastastic diseaseonly patients should be discussed only for those with a PCI < 12, who have no SC [39], and who are responsive to preoperative chemotherapy. Patients with small bowel involvement [40] and more than three liver metastases [41] should be excluded from surgical treatment.…”
Section: Summary Of Oligometastases From Colorectal Cancermentioning
confidence: 99%